William G. Bishop, Charter of the City of Brooklyn 192, § 16 (1877) - (:unkn) unknown (My University, 1877)
Ordinances of the City of Brooklyn § 16: No person shall carry, or cause to be carried, any gunpowder through any street, lane or alley in the city, unless the same be secured in tight casks, kegs or cases, well headed and hooped; and said casks, kegs or cases shall be put into and entirely covered with a bag or case sufficiently to prevent any said gunpowder from being spilled or scattered, under the penalty of forfeiture of the gunpowder and a fine of fifty dollars for every violation of the provisions of this act.
Keywords: GUNPOWDER - TRANSPORTATION